"Our Furniture Family": Frasier's Luxury Problems. Issue 1 (10th October 2016) - Gibbons, Sarah
Abstract: Frasier was a widely successful American sitcom that centered around its luxurious main character Frasier Crane and his eccentric family. Much of the comedy focused on character quirks and family dynamics, but this article argues that the objects within the Crane world were just as essential and illuminating as the characters themselves. From the first episode the set was utilized as a physical embodiment of Frasier's identity and class, as well as the anxieties that ensued whenever his identity was threatened. Utilizing Grant McCracken's concept of the Diderot effect and Diderot unity it is possible to explore the sitcom in a manner that deftly highlights how easy and all-consuming it can be to build and protect one's identity through the meticulous consumption of specific possessions. In the end, we find that it is not only Frasier who falls victim to this connection between possessions and identity, but all of us. Much like the set is a reflection of who Frasier is, Frasier, the sitcom, becomes a reflection of the viewer and our culture at large.